STATUS OF THE KAZAKH BRIDAL: TRADITIONS AND MODERNITY - Meirmanova, G.; Baudiarova, K. B.; Abashin, S. N. (Farabi Journal of Social Sciences, 2020)
In the article, the author clearly describes the role and etiquette of brides in Kazakhstani society. Ethnocultural education of Kazakh brides has entered their daily life. This has been the case in nomadic society for centuries. In the morning, they show respect by welcoming their parents and doing their daily routines - making tea early in the morning, setting the table, serving tea, cleaning the house, cooking, milking cows, entertaining guests, farming, and so on. The tradition of greeting is the respect and greeting of brides to their parents and in-laws. She greetings to other family members too. The bridegroom bowed down to greet the bridegroom's relatives. Shemakes tea and sets the table. The one who greets the bride expresses her gratitude to the bride. The bride wears a scarf in front of adults. It is also respect to adults.Forgiveness, understanding, helping each other in difficult momentare the tips that lead to happiness. As they say, "from the very beginning, the wife, from the age of the child," the boy's mother and father pay great attention to the bride's behavior, ability to do something and character. Because the customs in each country are different. Кeywords: etiquette, big house, shanyrak, mother-in-law.